The Effect of Salicylic Acid Antioxidant and Watering Intervals on Mitigating Drought Stress During the Vegetative Stage of Soybean ( Glycine max L. Merr.) - Abil Febriandi; Rahmadina Rahmadina; Khairunnisa Khairunnisa (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
Drought is one of thr abiotic factors that can hinder plant growth and productivity. The use of salicylic acid as an antioxidant is expected to enhance plant tolerance to water stress, while adjusting watering intervals serves as an effective water management strategy. This study aims to investigate the effect of salicylic acid application and watering intervals on the drought resistance of soybean plants (Glycine max L. Merr.) during the vegetative phase. This research employed an experimental method using a Randomize Complete Block Design (RCBD) with two treatment factors. The first factor was salicylic acid concentration at three levels: S0 (0 mM), S1 (1 mM) and S2 (2 mM). The second factor was watering interval with four levels: H0 (0-day interval), H1 (1-day interval), H2 (3-day interval) and H3 (5-day interval). Observed parameters included total leaf area, stomatal density, root dry weight, root volume, and canopy dry weight. The result showed that salylic acid concentration 1 mM treatment had a significant effect on total leaf area, stomatal density, root dry weight and canopy dry weight. Watering 5 day interval treatments significantly affected total leaf area and root volume. Meanwhile, the interaction between salicylic acid and watering treatment did not have a significant effect on any of the observed parameters